A Vehicle Trajectory Planning Method for Narrow Corridor in Mines Based on Optimal Control - LIN Xuerong; XIE Heping; XU Biao; YUAN Shijie; BIAN Yougang; HU Manjiang; QIN Zhaobo; HU Jiaxi (Kongzhi Yu Xinxi Jishu)
Due to the strictly restricted free area, vehicles have difficulties to pass through mine narrow corridors. To solve this problem, this paper presents a trajectory planning method based on optimal control. Narrow corridor model and vehicle single-track kinematics model are adopted to construct the trajectory planning model based on optimal control with an approximate space-discretization strategy considering factors like vehicle passage time, vehicle-boundary collision and vehicle actuator range. By vehicle kinematics integral, the control variable sequence solved by the above trajectory planning model leads to an initial optimal trajectory. Taking the discretization impact on trajectory continuity into account, the final target trajectory is formed after smooth the initial optimal trajectory by quadratic programming. Simulation results show that the trajectory generated by the proposed method is effective in narrow corridor scene, and the generated trajectory is continuous and smooth. Compared with the baseline method, the average maximum curvature reduces from 0.094 m-1 to 0.040 m-1 and the average passing time reduces from 6.18 s to 4.80 s in evaluate scenarios.